Mitigating Toxicity: Clinical and Pathological Effects of Ensiled Brachiaria decumbens in Sheep - Fauzi, Nurul Aishah Ahmad; Chung, Eric Lim Teik; Bakar, Nurul Adilah Abu; Kamalludin, Mamat Hamidi; Reduan, Mohd Farhan Hanif; Jesse, Faez Firdaus Abdullah; Dunshea, Frank R. (Malaysian Applied Biology, 2026)
Brachiaria decumbens, commonly known as signal grass, is widely used as livestock feed in tropical regions due to its high nutritional value and availability. However, its high concentration of steroidal saponins poses toxicity risks, raising concerns for small ruminant farmers. Therefore, this study aimed to evaluate the effect of feeding ensiled B. decumbens on the health and performance of sheep under tropical conditions. A total of eighteen six-month-old male Dorper cross sheep were used in a feeding trial and assigned to three treatment groups: the control group (T1), fed Pennisetum purpureum; Treatment 2 (T2), fed fresh B. decumbens; and Treatment 3 (T3), fed ensiled B. decumbens. Over the 98-day experimental period, clinical data were collected weekly. At the end of the study, all 18 sheep were slaughtered for morphometric, gross morphology, and histopathological analyses of their organs. The results revealed significant differences (p<0.05) in the health performance of sheep across feeding groups. Sheep in the T3 group, fed ensiled B. decumbens, exhibited slightly higher body weight gain compared to both the T2 group fed fresh B. decumbens and the control group (T1). Additionally, only T2 sheep exhibited pale ocular mucous membranes during the final 21 days of the study. In terms of organ morphometrics, T1 and T3 sheep had lower organ width, length, and weight compared to T2 sheep. Most vital organs appeared grossly normal across all treatments; however, post-mortem examination of T2 sheep revealed lung lesions, including congestion and pus accumulation in the caudal lobes. Histopathological analysis indicated mild to moderate lesions in various organs of T2 sheep fed fresh B. decumbens, whereas no lesions were observed in the T1 and T3 groups. This study concludes that incorporating ensiled B. decumbens into the diet of small ruminants yields more favorable health and performance outcomes than feeding fresh B. decumbens.